Synergistic enhancement of biohydrogen production by supplementing with green synthesized magnetic iron nanoparticles using thermophilic mixed bacteria culture - Abdul Aziz, Ainul Husna; Engliman, Nurul Sakinah; Mansor, Mariatul Fadzillah; Mohamed Abdul, Peer; Arisht, Shalini Narayanan; Jamali, Nur Syakina; Ming, Foong Tiang (Elsevier, 2022)
The production of biohydrogen can be improved by focusing on the nutrients needed by fermentative bacteria like iron. Iron reacts with the [Fe-Fe]-hydrogenase enzyme within the mixed bacteria culture for optimum hydrogen release. Iron nanoparticles (NPs) are attractive due to its unique properties and high reactivity. It can be produced through green synthesis, a more eco-friendly and relatively lower cost process, by using iron salt as precursor and green coconut shell extracted by deep eutectic solvent (DES) as reducing agent. The coconut shell extract consists of phytochemicals that help in producing polydisperse magnetic iron oxide nanoparticles at ~75 nm in size. The addition of optimum concentration of 200 mg Fe/L magnetic iron NPs resulted in the maximum cumulative hydrogen production, glucose utilization and hydrogen yield of 101.33 mL, 9.12 g/L and 0.79 mol H2/mol glucose respectively. Furthermore, the kinetic analysis on Gompertz model using the optimum magnetic iron NPs concentration showed that the hydrogen production potential (P) and hydrogen production rate (Rm) increased to 50.69 mL and 3.30 mL/h respectively and the lag phase time reduced about 7.12 h as compared with the control experiment (0 mg Fe/L). These results indicated the positive effects of magnetic iron NPs supplementation on fermentative biohydrogen production of mixed bacteria culture and proved the feasibility of adding the magnetic iron NPs as the micronutrient for enhancement of such hydrogen production system.